Achilles tendon and fascicle interaction during human running - Ichikawa, M.; Komi, P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
In human locomotion, skeletal muscle produces force and movement by utilizing the combination of muscle preactivation and subsequent eccentric-concentric actions. Stretching of activated muscles results in a significant force enhancement produced by muscle fibers and tendons. For exploring muscle mechanics, it has been a long time challenge among researchers to capture exactly and continuously the movements of the internal structures of the skeletal muscle, especially for during rapid movements. The purpose of the present study was to clarify that the fascicles of medial gastrocnemius (MG) muscles are stretched during running. This would then result in triggering the stretch reflex, which in turn could affect the power output of the fascicles and Achilles tendon (AT). Previous studies utilizing the ultrasound scanning do not necessarily support this concept (Lichwark and Wilson 2006, Kawakami and Fukunaga 2006). The high-speed ultrasonographic image scanning (169-199Hz, alpha-10, Aloka) for measuring the MG fascicle length and displacements of muscle-tendinous junction (MTJ) in MG was performed together with the electromyogram (EMG) recording during running at different speeds (n=8). Movements were recorded with the high-speed video camera (200 fps) to calculate the leg joint angles and to consider the calcaneus movements. The AT length was determined as the length from the MG MTJ to the AT insertion on the calcaneus. The results indicated that AT was indeed stretched and subsequently shortened during ground contact. However, this was preceded by the AT shortening phase 20-40ms after contact. The timing of this AT shortening was followed by the occurrence of the rapid MG fascicle stretching. Amplitude of this initial AT stretching increased proportionally with higher running speed and with higher MG preactivation. This suggests that AT can store elastic energy initially before muscle fibres become stretched beyond the limits of their short-range stiffness. However, AT can lose and/or transfer the stored elastic energy partially due to the rapid fascicle stretching. These events are apparently very transient. In the slower running conditions, the observed reflexinduced EMG activities during the early braking phase can influence the additional AT stretching and the rate of the force production in the braking phase. In the faster running condition, the observed reflex-induced EMG activities occur during the end of the braking phase and they can then influence the stretch-induced force potentiation during the push-off phase. Thus, AT does not behave a series of stretch-shortening cycle during ground contact of running. This is primarily due to the fascicle stretching beyond the limits of their short-range stiffness, and due to specific reflex contributions depending on the running speed.